2021
DOI: 10.1111/liv.14862
|View full text |Cite
|
Sign up to set email alerts
|

Is elimination of HCV realistic by 2030: France

Abstract: The World Health Organization (WHO) has proposed a plan for the elimination of viral hepatitis with a goal of reducing new hepatitis infections by 30% and 90% in 2020 and 2030, and associated mortality by 10% and 65% respectively. Actions and targets to reach these goals include improving hepatitis B virus (HBV) vaccination programs, the prevention of mother‐to‐child transmission of HBV, improving the safety of blood products and injections, risk reduction policies and optimizing the diagnosis and treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The introduction of direct‐acting antiviral (DAA) agents has reduced the development of hepatocellular carcinoma (HCC) and all‐cause mortality in chronic hepatitis C (CHC) patients 1,2 . Consequently, universal access to DAAs was implemented in August 2017 in France, following a priority access policy adopted in December 2013 restricting DAAs to patients with advanced liver disease and high‐risk populations 3 …”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of direct‐acting antiviral (DAA) agents has reduced the development of hepatocellular carcinoma (HCC) and all‐cause mortality in chronic hepatitis C (CHC) patients 1,2 . Consequently, universal access to DAAs was implemented in August 2017 in France, following a priority access policy adopted in December 2013 restricting DAAs to patients with advanced liver disease and high‐risk populations 3 …”
Section: Purposementioning
confidence: 99%
“…1,2 Consequently, universal access to DAAs was implemented in August 2017 in France, following a priority access policy adopted in December 2013 restricting DAAs to patients with advanced liver disease and high-risk populations. 3 It is now well established that HCV-induced immune dysregulation and persistent inflammation explain the occurrence of several extrahepatic manifestations. [4][5][6] In particular, HCV infection is recognized as a risk factor for the development of several cardiovascular diseases.…”
Section: Purposementioning
confidence: 99%
“…The prevalence of chronic HCV infection among PWIDs is approximately 40%. A major barrier to the French national goal ‘2025 without Hepatitis’ 1,8–10 is that many patients are unaware of their status.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some patients received DAAs before the universal access to DAAs in France or as part of clinical research protocols that could not be identified in the SNDS. As many DAAs are now also dispensed in pharmacies, they are now better recorded in the SNDS 33 . It is, therefore, expected that the actual performance of the algorithms for identifying CHC patients treated with antivirals will be higher.…”
Section: Discussionmentioning
confidence: 99%
“…As many DAAs are now also dispensed in pharmacies, they are now better recorded in the SNDS. 33 It is, therefore, expected that the actual performance of the algorithms for identifying CHC patients treated with antivirals will be higher.…”
Section: Discussionmentioning
confidence: 99%